Protocol for an Open Labelled Parallel Comparative Clinical Study to Evaluate the Efficacy of Karkashdaladi Kwath and Navaka Guggulu in the Management of Medodushti with Special Reference to Dyslipidemia - Dr. Charu Walia; Dr. Neelam Kumari; Dr. Neha Lamba (International Journal for Research in Applied Science and Engineering Technology, 2026)
Background: Dyslipidemia can be correlated with Medodushti as described in Ayurveda. It is characterized by abnormal lipid metabolism and is highly prevalent worldwide. Dyslipidemia is one of the major modifiable risk factors for diabetes mellitus, obesity, chronic heart diseases, and thyroid disorders. Although statins are the treatment of choice in modern medicine, their long-term use may be associated with several adverse effects. Therefore, there is a need to explore safe and effective Ayurvedic interventions for its management. Objective: To evaluate and compare the clinical efficacy of Karkashdaladi Kwath and Navaka Guggulu in the management of Medodushti w.s.r to Dyslipidemia. Methods: A single-centered, open-labelled, parallel comparative clinical trial will be conducted on 60 patients (aged 25–45 years) diagnosed with Medodushti. Participants will be randomized into two groups (n = 30 each). GroupA Karkashdaladi kwath (50ml twice daily) and Group-B), Navaka Guggulu (500 mg twice daily).The treatment will continue for 28 days. Outcome assessments include subjective parameters (dyspnoea, thirst etc.) and objective parameters (T. Cholestrol, triglyceride, LDL etc). Follow-up evaluations on days 7th, 14th, 21st, 28th during treatment and days 42nd and 56th post-treatment. Statistical significance is set at p < 0.05. Expected Results: Both formulations will anticipated to improve clinical indices and biochemical data related to Dyslipidemia in Medodushti patients. However, Karkashdaladi Kwath is hypothesized to yield a superior efficacy because of its Strotovishodhana (channel cleansing), Aamapachana (digestion of metabolic toxins) properties. Conclusion: This study may validate evidence-based Ayurvedic alternative to conventional treatment, supporting the integration of traditional formulations into mainstream management protocols.